A Comparison of the Diagnostic Efficiency of Ultrasound Guided Fine Needle Aspiration Cytology versus Conventional Fine Needle Aspiration Cytology of the Thyroid (Bangladesh Journal of Otorhinolaryngology, 2025)
Background: In case of thyroid lesion conventional FNAC (C-FNAC) is most reliable and convenient investigation. But it has high inadequate sample collection rate. Ultrasound guided FNAC (US-FNAC) one of the alternative to investigate a thyroid swelling more appropriately.Objectives: Aim of this study to evaluate the diagnostic precision of C-FNAC and weigh up with US-FNAC as well as histopathology.Methods: In this study, a total of 200 patients divided into two groups (A& B) presenting with thyroid swelling or nodules underwent C-FNAC for group A and US-FNAC for group B with subsequent surgery from January 2022 to December 2023 at Green Life Hospital. Cytological diagnosis was classified according to the Bethesda classification. Final histopathological results were compared to find out the accuracy of C-FNAC and US-FNAC.Results: From group A we found 7% nondiagnostic and in group B 1% due to inadequate sample. In term of sensitivity, C-FNAC counted 66.7% and US-FNAC 85.2% and in specificity it was 92.8% and 98.6% respectively. In C-FNAC false negative rate was 33.3% where it was 14.8% in US-FNAC. Finally the accuracy was 95% in US-FNAC where it was 85% in C-FNAC.Conclusions: C-FANC is very simple and useful tool for diagnosis of thyroid lesion. But for more precise and specific diagnosis US-FNAC is more superior due to additional information gathered from ultrasound examination along with well visualized aspiration from the targeted lesion.Bangladesh J Otorhinolaryngology 2025; 31 (1) Page-28-34